The ABC transporter A7 modulates neuroinflammation via NLRP3 inflammasome in Alzheimer’s disease mice - Irene Santos-García; Pablo Bascuñana; Mirjam Brackhan; María Villa; Ivan Eiriz; Thomas Brüning; Jens Pahnke (Alzheimer’s Research & Therapy)
Abstract Background Specific genetic variants in the ATP-binding cassette transporter A7 locus (ABCA7) are associated with an increased risk of Alzheimer’s disease (AD). ABCA7 transports lipids from/across cell membranes, regulates Aβ peptide processing and clearance, and modulates microglial and T-cell functions to maintain immune homeostasis in the brain. During AD pathogenesis, neuroinflammation is one of the key mechanisms involved. Therefore, we wanted to investigate the specific role of ABCA7 in microglial activation via the NLRP3 inflammasome. Methods We developed the first humanized, Cre-inducible ABCA7 flx knock-in mouse model, crossbred it with the APPPS1-21 β-amyloidosis model, and generated constitutive ABCA7ko and microglia Cx3cr1-specific conditional ABCA7ko AD mice. The role of ABCA7 was analyzed using histological, biochemical, molecular and mass spectrometry methods. Results Constitutive knockout of the Abca7 gene in APPPS1 mice increased the levels of Aβ42 and the number of IBA1+ (microglia) and GFAP+ (astrocytes) cells. Changes in the levels of astrocytes and microglia are associated with the activation of the NLRP3 inflammasome and increased levels of proinflammatory cytokines, such as IL1β and TNFα. Interestingly, microglia-specific ABCA7ko restored Aβ42 peptide levels and IBA1+ and GFAP+ and NLRP3-related gene expression to the original APPPS1 mouse levels. In primary glial cell cultures of APPPS1-hA7ko microglia and APPPS1 astrocytes from newborn pups, we observed that conditioned media from LPS-stimulated microglia was able to induce NLRP3 inflammasome expression and proinflammatory cytokine release in astrocytes. Conclusions Our data suggest that ABCA7 transporters regulate the communication between microglia and astrocytes through the NLRP3 inflammasome and the release of proinflammatory cytokines. This regulation implicates ABCA7 as a key driver ultimately involved in the persistence of the inflammatory response observed in AD.